Investıgatıon On The Effects Of Acıdıc Drınks To Shear Forces On Metal Brackets: An Invıtro And Invıvo Research - Ali Vehbi Tuncer; Gökhan Önçağ; Yahya Tosun (Galenos Yayinevi, 2000)
In our study, effects of acidic drinks on bracket debonding subjected to shear forces on teeth that are bonded with brackets in fixed orthodontic treatment. 60 non-carious premolars which were extracted for orthodontic purposes are gathered in invivo and invitro groups. In both groups, teeth are divided equally in three subgroups as Coca-Cola, Sprite and Control groups. Brackets are bonded by using the same method and bonding material. Teeth that are in invit ro group are kept in acidic drink for 5 minutes in 3 equal time intervals within 24 hours. This procedure is continued for 3 months. Teeth that are in invivo group are bonded in the same manner as in invitro group. Those teeth were planned to be extracted for orthodontic purposes. Patients are instructed to rinse with the acidic drink 3 times for 5 minutes daily. Patients are told not to drink any other acidic drink. After 3 months, teeth are extracted without damaging the brackets. All samples in invivo and invitro groups are subjected to shearing procedure on Universal test machine with 0.5mm/min. velocity. Our results show that, acidic drinks cause less debonding resistance in both invivo and invitro groups compared to control group. And no statistical differences were found experimentally between invivo and invitro media.